Common and rare genetic risk variants in age‐related macular degeneration and genetic risk score in the Coimbra eye study. Issue 2 (29th August 2022) - Farinha, Cláudia; Barreto, Patricia; Coimbra, Rita; Cachulo, Maria Luz; Melo, Joana Barbosa; Cunha‐Vaz, José; Lechanteur, Yara; Hoyng, Carel B.; Silva, Rufino
Abstract: Purpose: To determine the contribution of common and rare genetic variants in age‐related macular degeneration (AMD) in a Portuguese population from the Coimbra Eye Study (CES), and the genetic risk score (GRS). Methods: Participants underwent ophthalmologic examination and imaging. A centralized reading centre performed AMD staging. Genetic sequencing was carried out with the EYE‐RISK assay. Sixty‐nine single nucleotide polymorphisms (SNPs) were genotyped and tested for association with AMD. Case–control and progression‐to‐AMD analyses were performed using logistic regression to assess allelic odds ratio (OR) at a 95% confidence interval (CI) for each variant. GRS was calculated for cases/controls and progressors/non‐progressors. Cumulative impact of rare variants was compared between cases/controls using logistic regression. Results: In case–control analysis (237 cases/640 controls) variants associated with risk of disease were: ARMS2 rs10490924, ARMS2_HTRA1 rs3750846, CFH rs35292876, SLC16A8 rs8135665, TGFBR1 rs1626340. Major risk variants ARMS2/HTRA1 rs3750846, CFH rs570618 and C3 rs2230199 had unexpected lower allele frequency (AF), and the highest risk‐conferring variant was a rare variant, CFH rs35292876 (OR, 2.668; p ‐value = 0.021). In progression‐to‐AMD analysis (137 progressors/630 non‐progressors), variants associated with risk of progression were ARMS2 rs10490924, ARMS2_HTRA1 rs3750846, CFH rs35292876. GRS of cases/controls was 1.124 ± 1.187 and 0.645 ± 1.124 ( p ‐value < 0.001), and of progressors/non‐progressors was 1.190 ± 1.178 and 0.669 ± 1.141 ( p ‐value < 0.001). Higher proportion of pathogenic rare CFH variants was observed in cases (OR, 9.661; p ‐value < 0.001). Conclusions: Both common and rare variants were associated with AMD, but a CFH rare variant conferred the highest risk of disease while three major risk variants had a lower‐than‐expected AF in our population originary from a geographic region with lower prevalence of AMD. GRS was still significantly higher in AMD patients. Damaging CFH rare variants were cumulatively more common in AMD cases.